Analisis Pengaruh Pemahaman Peraturan, Sanksi, Tarif, dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak di E-Commerce (Studi Kasus Terhadap Pengusaha di Platform Online Shopping) - Luthfiyah, Mitha Faridatul; Mawardi, M. Cholid; Sari, Arista Fauzi Kartika (e_Jurnal Ilmiah Riset Akuntansi, 2023)
The Indonesian government has been motivated to control the tax aspects of the E-commerce transactions to optimize future tax collection due to the increasing expansion of E-commerce in the country. Tax revenue from E-Commerce entrepreneurs has not achieved 100% despite the fact that the tax sector produces more revenue than any other sector due to a number of ongoing challenges, such as low tax sanctions, high tax rates, taxpayer ignorance that may impact taxpayer compliance, and lack of understanding of tax regulations. This study looks at how taxpayer compliance of E-Commerce users is affected by their knowledge of tax regulations, tax sanctions, tax rates, and taxpayer awareness. By using purposive sampling methodology, a quantitative approach with a total of 130 respondents. This study found that taxpayer understanding, tax rates, tax penalties, and tax regulation understanding have an impact on how compliant e-commerce users are. The factors of tax rates and taxpayer awareness do not have a substantial impact on taxpayer compliance of E-Commerce users, but the variables of understanding tax regulations and tax penalties have a positive and significant effect on the compliance of E-commerce user taxpayers.Keywords: Taxpayer compliance, taxpayer awareness, tax regulations understanding, tax penalties, tax rates.